Microfinance for Women Empowerment: A Review of Best Practices - Lamichhane, Basu Dev (Interdisciplinary Journal of Management and Social Sciences, 2020)
The purpose of the paper is to highlight the role of microfinance for women empowerment. The study is a descriptive study design. Many developmental activities and programs are implemented in the society but microfinance programs are strong rural based and deprived women oriented and targeted to the marginalized people. Microfinance is an effective and powerful instrument for women empowerment. The number of challenges ahead of women empowerment are poor economic status, illiterate, unskilled, unemployment, low access in land, housing, transportation, electricity and family decision. It is considered as one of the most effective poverty alleviation tools. Microfinance services are considered as an entry point or vehicle towards empowering women. Members of microfinance institution (MFIs) have more contribution to saving and income generating activities, household decision making and activities beyond household sector. Although many programs have been implemented for poverty alleviation, only microfinance programs are seen as poor and rural women based. Microfinance is one of the best alternatives to generate self-employment specially the poor women in the rural areas. It provides services to them who have no collateral to offer against the loans. Women who could gain access to microfinance services have been able to create self-employment opportunities and have been economically and socially empowered through increased income through small projects. Microfinance has a profound impact on the economic status, decision making power, knowledge and self-worthiness of women, community activities and self-help group programs. The study reveals that there is a positive relationship between microfinance and women empowerment. Microfinance becomes catalyst for social change and women’s empowerment.